Freeze casting of porous monolithic composites for hydrogen storage. Issue 24 (4th November 2022) - Neville, George M.; Jagpal, Rajan; Paul-Taylor, Joseph; Tian, Mi; Burrows, Andrew D.; Bowen, Chris R.; Mays, Timothy J.
Abstract : Freeze casting of composite PIM-1 and activated carbon hydrogen adsorbent monoliths, from chloroform, toward high-strength pressure vessel inserts. Abstract : Hydrogen storage by adsorption offers operational benefits over energy intensive compression techniques. Incorporating physisorption materials in compression stores could improve hydrogen capacities, reducing the volume or pressure needed for storage vessels. However, such materials are often presented as fine powders and development efforts to date have predominantly focused on improving hydrogen uptake alone. Without due attention to industry-relevant attributes, such as handling, processability, and mechanical properties it is unlikely that these materials will find commercial application. In the paper, the desirable mechanical properties of hydrogen-adsorbent PIM-1 are exploited to yield a series of composite monoliths doped with a high surface area activated carbon, intended to act as pressure vessel inserts. Freeze casting techniques were successfully adapted for use with chloroform, facilitating the production of coherent and controlled three-dimensional geometries. This included the use of an innovative elastomeric mould made by additive manufacture to allow facile adoption, with the ability to vary multiple forming factors in the future. The composite monolith formed exhibited a stiffness of 0.26 GPa, a compressive strength of 6.7 MPa, and an increased BET surface area of 847 m 2 g −1 compared to PIM-1 powders, signifying the first steps towards producing hydrogen adsorbents in truly useful monolithic forms.